Small Cash Information Systems And Web-Based Bank Transactions At PT. Sky Alloys International: Small Cash Information Systems And Web-Based Bank Transactions At PT. Sky Alloys International - Dedi Setiadi; Mohamad Subchan (Institute of Computer Science (IOCS), 2020)
Currently, the entry of financial transaction data that is taking place at PT. Sky Alloys International is done manually by financial staff. Financial transactions can only be done on a computer at PT. Sky Alloys International only, so if the financial staff or the person concerned is outside PT. Sky Alloys International, so it cannot make transactions. This is an obstacle for managers, because these data are very important to know the current financial situation at PT. Sky Alloys International. Seeing the problems that occur, it is necessary to make petty cash accounting applications and bank transactions that can help the work of the finance department and managers in viewing financial information. In this application there are accounting logics used to calculate transactions and balances of the account used. The results of this application are financial reports shown to the manager. In the end, this application can help the work of the finance department in entering transactions and managers in viewing financial reports.